To study the effectiveness of export promotion by Malaysian External Trade and Development (MATRADE) / Mohd Amirul Mohd Syafiq - Mohd Syafiq, Mohd Amirul (Faculty of Business and Management, 2014)
Purpose-Export performance is really important for the firms in order to identify their strength. One of the strategies is to export. MATRADE, a national trade agency offer various support for these firm to export. Thus the purpose of this research is to find out how effective the export promotion programs on export performance of the firms.